Propostas de utilização de sequências didáticas investigativas para o estudo do conceito de velocidade no ensino médio - Pereira, Whortton Vieira (2014)
The misconception’s evolution to the scientific knowledge is a long process. In this way, several authors pointed that investigative experimental activities would promote conceptual evolution. In this work, a study was performed in order to investigate the utilization of investigative experimental activities as a tool to achieve conceptual evolution. The addressed concept was velocity. The sequence of activities was accomplished with a group of first year high school students who had already studied the concept of speed. In this group many students presented misconceptions reported in the literature. In this case, misconceptions were perceived even after the formal instruction. As discussed in the literature a single activity was not sufficient to promote the conceptual evolution. Because of this, it was necessary tree different activities. After these activities, all students answered questions, and the students responses were analyzed by contend analyses. The data analyses corroborated that experimental investigative activities would be a good alternative compared to traditional laboratory classes.